2006
DOI: 10.1017/s0022112005007366
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a synthetic jet acting on a separated flow over a hump

Abstract: The effects of an oscillatory zero-net-mass-flux jet (i.e. synthetic jet) acting on a separated flow over a hump are investigated in terms of two actuation parametersactuator position and forcing frequency. By considering the vorticity flux balance and introducing a centroid of vorticity production over the hump surface, lift and drag acting on the hump can be expressed as a function of this centroid and the rate of vorticity production. To study the parametric dependence of lift and drag, direct numerical sim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 43 publications
0
9
0
Order By: Relevance
“…As a result, the surface curvature is discontinuous at the junctions between the actuator exit and the airfoil surface. In the present study, the SJ is simply modeled by the time-periodic velocity boundary conditions at the actuator exit, [11][12][13]18,24 instead of a cavity-type actuator where the jet is realized by the piston stroke in the cavity. 17,20,33,38 Although phase lag exists between the piston velocity and the jet velocity, 23 and the jet will undergo viscous dissipation, we mainly focus on the effects of jet on flow separation control and neglect the implementation details of a synthetic jet.…”
Section: A Physical Setupmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, the surface curvature is discontinuous at the junctions between the actuator exit and the airfoil surface. In the present study, the SJ is simply modeled by the time-periodic velocity boundary conditions at the actuator exit, [11][12][13]18,24 instead of a cavity-type actuator where the jet is realized by the piston stroke in the cavity. 17,20,33,38 Although phase lag exists between the piston velocity and the jet velocity, 23 and the jet will undergo viscous dissipation, we mainly focus on the effects of jet on flow separation control and neglect the implementation details of a synthetic jet.…”
Section: A Physical Setupmentioning
confidence: 99%
“…The SJ resulted in an approximately 30% reduction of the time-averaged size of the separation zone, in reasonable agreement with the experimental value of 28%. Suzuki 18 performed a similar 2D simulation on a semi-circular cylinder at Reynolds number Re r = 4 × 10 3 . He observed that the periodic forcing by the jet breaks the large-scale separated vortices into smaller ones, delaying the separation point and resulting in an improved aerodynamic performance.…”
Section: Introductionmentioning
confidence: 99%
“…Seifert and Pack [64] argued that the optimum control could be achieved when there were four small scale vortices in the separation region, which resulted in the optimum dimensionless exciting frequency 1.0. Suzuki [65] studied the effects of an oscillatory ZNMF jet acting on the flow over a half-cylindrical hump in two dimensions. The DNS results have shown that periodic actuation breaks large-scale vortices that are generated in the natural case into smaller vortices and delays the separation point at the dimensionless frequency St =1, but they found that there was no improvement for the aerodynamic performance when the actuator frequency was in the range of St=O (10), which is the optimum frequency found by Amitay and Glezer [54,55] to control the separation of the flow around an unconventional airfoil.…”
Section: Figure 22mentioning
confidence: 99%
“…The DNS results have shown that periodic actuation breaks large-scale vortices that are generated in the natural case into smaller vortices and delays the separation point at the dimensionless frequency St =1, but they found that there was no improvement for the aerodynamic performance when the actuator frequency was in the range of St=O (10), which is the optimum frequency found by Amitay and Glezer [54,55] to control the separation of the flow around an unconventional airfoil. Suzuki [65] suggested that the reason is that the laminar flow simulations lack some features of a turbulent boundary layer, and the natural separation phenomenon is different for two-and three-dimensional bodies. Dandois et al [66] performed numerical simulations of the controlled flow over a smooth ramp to study the influence of ZNMF jet frequency by solving the N-S equations with LES/DNS.…”
Section: Figure 22mentioning
confidence: 99%
“…Therefore, Suzuki conducted the study of the synthetic jet that applied to the two dimensional flow over a hump. 1 In this study, some appropriate parameters of the synthetic jet were obtained for a separation control as a result of the detailed analysis of the flow field.…”
Section: Introductionmentioning
confidence: 99%